A Substantial Role of Agro-Textiles in Agricultural Applications - Sharma, Neha; Allardyce, Ben; Rajkhowa, Rangam; Adholeya, Alok; Agrawal, Ruchi (Frontiers in Plant Science, 2022)
Agro-textiles have been used in the agriculture sector for thousands of years and are an attractive tool for the protection of crops during their entire lifecycle. Currently, the agro-textiles market is dominated by polyolefin's or petrochemical based agro-textiles. However, climate change and increase in greenhouse gas emissions have raised concern about the future oil-based economy and petroleum-based agro-textiles have become expensive and less desirable in the modern world. Other products are the agro-textiles based on the natural fibres which degrade so fast in the environment that their recovery from the fields becomes difficult and unattractive even by efficient recycling or combustion and their lifetime is usually limited to one or maximum of two years. Hence, the development of biobased agro-textiles with a reduced impact on the environment and with extended durability is foreseen to initiate the growth in the biobased economy. The world is gradually preparing the shift towards a biobased economy, and research for sustainable bio-based alternatives has already been initiated. This review provides insight into the various agro-textiles used currently in agriculture and the research going on in the area of agro-textiles to offer alternative solutions to the current agro-textiles market.